1994
DOI: 10.1212/wnl.44.3_part_1.499
|View full text |Cite
|
Sign up to set email alerts
|

A clinical genetic study of Parkinson's disease

Abstract: We used a family history questionnaire, semi-structured interview, and personal examination of secondary cases to collect data on the prevalence of Parkinson's disease (PD) in relatives of patients seen consecutively for 1 year and assessed the proportion of secondary cases of PD as a function of pedigree completeness. Survival analysis methods were applied to estimate the lifetime risk and age-at-onset distribution of PD among first-degree relatives of probands. When we considered siblings of probands with af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
2
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 0 publications
3
67
2
6
Order By: Relevance
“…This finding is in agreement with previous clinic-based studies (based on family history accounts of patients). 2 ' 7,8 Fourth, the magnitude of increasing risk of PD mirrors that expected on the basis of shared genetic makeup with the proband, that is, first degree relatives have a greater risk than second degree relatives by approximately eight-fold. However, this finding must be considered carefully as other explanations, such as a possible case ascertainment bias favoring first degree relatives, may be important in explaining the disparity in prevalence between first and second degree relatives.…”
Section: Le Journal Canadien Des Sciences Neurologiquesmentioning
confidence: 97%
“…This finding is in agreement with previous clinic-based studies (based on family history accounts of patients). 2 ' 7,8 Fourth, the magnitude of increasing risk of PD mirrors that expected on the basis of shared genetic makeup with the proband, that is, first degree relatives have a greater risk than second degree relatives by approximately eight-fold. However, this finding must be considered carefully as other explanations, such as a possible case ascertainment bias favoring first degree relatives, may be important in explaining the disparity in prevalence between first and second degree relatives.…”
Section: Le Journal Canadien Des Sciences Neurologiquesmentioning
confidence: 97%
“…Several case-control studies have consistently indicated that PD is more common among relatives of index patients with PD compared with a matched control population, as between 6 and 30 % of index patients had first-or seconddegree affected relatives (Lazzarini et al 1994 ;Payami et al 1994 ;Bonifati et al 1995 ;De Michele et al 1996 ;Marder et al 1996). However, these studies were subject to recall bias.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…In many cases a heritable factor predisposes to the development of the clinical syndrome (2). We have recently shown that genetic markers on human chromosome 4q21-q23 segregate with the PD phenotype in a large family of Italian descent (3).…”
mentioning
confidence: 99%